MANAJEMEN STRATEGIK PEMASARAN UNTUK MENINGKATKAN MINAT MAHASISWA DI UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG DAN UIN MALIKI IBRAHIM MALANG - Desi Dwi Anissa; Mukhamad Sukur (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Islamic higher education in Indonesia, particularly UIN Sayyid Ali Rahmatullah Tulungagung and UIN Maulana Malik Ibrahim Malang, faces challenges in increasing student interest and educational quality amidst increasingly fierce competition. This study aims to analyze effective digital marketing strategies to strengthen the attractiveness of both institutions through a strategic management approach based on SWOT analysis. The research method used is descriptive qualitative with data collection techniques through in-depth interviews with leaders, marketing staff, and lecturers at both campuses, as well as focus group discussions (FGDs) with students and alumni. The results reveal that UIN Malang has a more structured digital marketing system with a professional team and adequate infrastructure, while UIN Tulungagung is still in the capacity development stage. The optimal implementation of the 4P digital marketing mix can increase campus visibility, engagement, and student enrollment. However, increased human resource and technology capacity as well as internal coordination are needed for better effectiveness, especially for UIN Tulungagung. These findings provide a strategic contribution to the development of adaptive digital marketing management in Islamic universities, while strengthening the position of both campuses in the national higher education competition